Genetically decreased vitamin D and risk of Alzheimer disease. (13th December 2016) - Mokry, Lauren E.; Ross, Stephanie; Morris, John A.; Manousaki, Despoina; Forgetta, Vincenzo; Richards, J. Brent
Abstract : Objective: To test whether genetically decreased vitamin D levels are associated with Alzheimer disease (AD) using mendelian randomization (MR), a method that minimizes bias due to confounding or reverse causation. Methods: We selected single nucleotide polymorphisms (SNPs) that are strongly associated with 25-hydroxyvitamin D (25OHD) levels ( p < 5 × 10 −8 ) from the Study of Underlying Genetic Determinants of Vitamin D and Highly Related Traits (SUNLIGHT) Consortium (N = 33, 996) to act as instrumental variables for the MR study. We measured the effect of each of these SNPs on 25OHD levels in the Canadian Multicentre Osteoporosis Study (CaMos; N = 2, 347) and obtained the corresponding effect estimates for each SNP on AD risk from the International Genomics of Alzheimer's Project (N = 17, 008 AD cases and 37, 154 controls). To produce MR estimates, we weighted the effect of each SNP on AD by its effect on 25OHD and meta-analyzed these estimates using a fixed-effects model to provide a summary effect estimate. Results: The SUNLIGHT Consortium identified 4 SNPs to be genome-wide significant for 25OHD, which described 2.44% of the variance in 25OHD in CaMos. All 4 SNPs map to genes within the vitamin D metabolic pathway. MR analyses demonstrated that a 1-SD decrease in natural log–transformed 25OHD increased AD risk by 25% (odds ratio 1.25, 95% confidence interval 1.03–1.51, p = 0.021). After sensitivity analysis in which we removed SNPs possibly influenced by pleiotropy and population stratification, the results were largely unchanged. Conclusions: Our results provide evidence supporting 25OHD as a causal risk factor for AD. These findings provide further rationale to understand the effect of vitamin D supplementation on cognition and AD risk in randomized controlled trials.